Spectral and temporal holograms with nonlinear optics - Shiloh, Roy; Arie, Ady (Optics Letters, 2012)
In this Letter we show how encoding techniques for computer-generated holograms may be used to arbitrarily shape a nonlinearly generated spectrum and consequently the temporal shape by modulating the quadratic nonlinear coefficient. We give examples of a modulation pattern and a simple setup that can generate high-order Hermite-Gauss and Airy functions through difference-frequency generation from a transform-limited Gaussian pulse, under practical fabrication considerations. © 2012 Optical Society of America.
Created from Fastlane, Scopus look-up